Surgical treatment of acute hemorrhagic gastritis - Duran, Manuel (Cirugía del Uruguay, 1974)
An analysis was made of the different methods employed in treating hemorrhages due to gastritis, keeping to recommendation of medica! treatment in mild cases, and the necessity of pre-operatory diagnosis by means of radiological and endoscopical examination. According to the evidence obtained and the characteristics of the hemorrhage, the patient should be submitted to vagotomy with a pyloroplastia and antrectomy, or simply a sub-total gastrectomy.